2012
DOI: 10.1177/0021998312465765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characteristics of continuous basalt fiber reinforced aluminum matrix composites

Abstract: This study, for the first time investigates the applicability of basalt fiber as a reinforcing material for metal matrix composites through various experimental works for thermal stability and mechanical properties. The residual tensile strength values of basalt fibers after being exposed at different temperatures in a furnace for pre-determined times and/or after being immersed into molten aluminum for different lengths of time were evaluated. Throughout these experimental studies, a processing method for fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Basalt fiber (BF) is a new fiber material with a high inorganic environmentally friendly green performance. Compared with other fibers (glass fiber and steel fiber), basalt fiber has better corrosion resistance, a higher elastic modulus, better chemical stability, impact resistance, and fire resistance [5,6]. Basalt fiber was originally used in military and aerospace research programs [7,8] and is now widely used as a structural reinforcement material in buildings [9][10][11], bridges [12,13], highways [14,15], tunnels [16,17], and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fiber (BF) is a new fiber material with a high inorganic environmentally friendly green performance. Compared with other fibers (glass fiber and steel fiber), basalt fiber has better corrosion resistance, a higher elastic modulus, better chemical stability, impact resistance, and fire resistance [5,6]. Basalt fiber was originally used in military and aerospace research programs [7,8] and is now widely used as a structural reinforcement material in buildings [9][10][11], bridges [12,13], highways [14,15], tunnels [16,17], and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present work is to investigate the effects of desizing by heat treatment on the mechanical properties of commercial basalt-based natural fibers. The tensile properties of single fibers are measured after two heat treatments in air: the first one at low temperature (350°C, representative of the maximum in-use temperature of polymer matrix composites [17]) and the second one at high temperature (600°C, representative of the processing of metal matrix composites [18]). The treatment times are determined by isothermal thermogravimetric analysis in order to obtain a complete desizing of the fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result showed that the volume loss is greater in 6061Al/Al2O3 composites when compared to 7075Al/SiC composites. Akhlaghi et al [10] investigated the applicability of basalt fiber as a reinforcing material in metal matrix composites through various experimental works. They found that from micro structural studies a good bonding between aluminum and basalt together with a reasonably uniform distribution of fibers within the matrix alloy.…”
Section: Introductionmentioning
confidence: 99%